Linguistic Complexity, Speech Production, and Comprehension in Parkinson’s Disease: Behavioral and Physiological Indices - Walsh, Bridget (2010)
PURPOSE: To investigate the effects of increased syntactic complexity and utterance length demands on speech production and comprehension in individuals with Parkinson’s disease (PD) using behavioral and physiological measures. METHOD: Speech response latency, interarticulatory coordinative consistency, accuracy of speech production, and response latency and accuracy on a receptive language task were analyzed in 16 individuals with PD and 16 matched control participants. RESULTS: Individuals with PD had higher oral motor coordination variability, took a longer time to initiate speech, and made more errors on the speaking task compared with the control group. They also received lower scores on the 2 complex conditions of the receptive language task. Increased length and syntactic complexity negatively affected performance in both groups of speakers. CONCLUSIONS: These findings provide a novel window into the speech deficits associated with PD by examining performance on longer, sentence-level utterances in contrast to earlier investigations of single-word or nonword productions. Speech motor control processes and language comprehension were adversely affected in the majority of our participants with mild to moderate PD compared to the control group. Finally, increased syntactic complexity and sentence length affected both the healthy aging and PD groups’ speech production performance at the behavioral and kinematic levels.